A Robust Cumulative Sum for Monitoring High-Risk Stock in Malaysia (Journal of Computational Innovation and Analytics (JCIA), 2025)
This study analyzes stock price fluctuations and develops a robust monitoring approach for high-risk stocks. It identifies key factors influencing stock price volatility, constructs a median CUSUM control chart as an alternative to the mean CUSUM chart, which requires a normality assumption unsuitable for stock price data, and compares the median CUSUM chart’s performance during and after COVID-19. A Fishbone diagram is used to determine factors contributing to stock price fluctuations, while a risk matrix helps identify high-risk stocks. The median CUSUM control chart is then applied to monitor stock performance, focusing on FINTEC Global Berhad. Findings indicate that during and after COVID-19, FINTEC’s stock performance declined due to financial management challenges that affected investor sentiment. The study highlights the effectiveness of the median CUSUM chart in detecting small shifts in stock fluctuations compared to the mean CUSUM chart. This approach provides a more reliable framework for monitoring stock risk and volatility. By integrating quality tools such as the Fishbone diagram and risk matrix, this study enhances risk assessment strategies in financial market analysis, offering valuable insights for investors and analysts navigating uncertain market conditions.